Sharḥ al-Talwīḥāt al-lawḥiyya wal-ʿarshiyya. Volume 3 : al-Ilāhiyyāt - Kammūna, Ibn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Shihāb al-Dīn al-Suhrawardī (d. 587/1191) is arguably the most influential thinker in post-Avicennan (d. 428/1037) philosophy. He is best known as the originator of the Philosophy of Illumination, a mixture of Hellenistic, old-Iranian, and mystico-Islamic elements, further developed and transformed in the Transcendental Philosophy of Mullā Ṣadrā (d. 1050/1640). Suhrawardī wrote four major works on the Philosophy of Illunination: al-Talwīḥāt al-lawḥiyya wal-ʿarshiyya , al-Muqāwamāt, al-Mashāriʿ wal-muṭāraḥāt , and the Ḥikmat al-ishrāq . This was also the order in which these works had to be studied. The Talwīḥāt being an introductory course on the Philosophy of Illumination, it is not surprising that three commentaries on it were written, by ʿAllāma Ḥillī (d. 726/1326), Shams al-Dīn al-Shahrazūri (d. 687/1288), and Ibn Kammūna (d. 683/1284), whose commentary is published here. Ibn Kammūna was a thinker of Jewish origin who by his own declaration was self-taught in philosophy. He wrote several other important philosophical works, among them his commentary of Avicenna's Ishārāt . Volume 3, Metaphysics.